(3MGTjI Ydi MceI GdYjf ddbRhjfjs - (3GdMfaj GdYdhj GdOgdhj, ejQRGLGf (B- (3TeS GdOjf, MHjH Gddg Hf YHO Gddg, J (B994 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd GdTjN (B: (3GdMceI GSJceGd GdfaS GdEfSGfjI HJMUjd eG Ydjg GdhLhO heG Ydjg GdhGLH eeG jfHZj Cf Cbhd GdGSJceGd eUOQ hGdeUGOQ bO JWdb hjQGO HgG eYGfjgG GdfSHjIs
(3BNQgG (B:s
(3hGdGJUGa GdPj gh fSHI HjfgeG hgPg CehQ KdGKI cd efgG HSjWI adh de jcf TjA ef gPg GdHSGjWs
(3aj Chdg fbhd HGdaQGSjI (B- (3hHg WjGQGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/167s
(3eYLe GdeDdajf (B1/527s
(3cTa GdXfhf (B1/685s
(3gOjI GdYGQajf (B1/262s
Keywords: (3GdadSaI hGdefWbs